The influence of financial leverage on bid-ask spread through market capitalization: A study on companies listed in LQ 45 index - Muhammad Putra Aprullah; Muhammad Arfan; Syukriy Abdullah (Proceedings of AICS - Social Sciences, 2013)
This study is aimed to examine empirically the influence of financial leverage on bid-ask spread through market capitalization. The population are companies that listed in the LQ45 Index during periods 2011-2012. This study uses 35 companies listed in the LQ45 index during periods 2011-2012 as many as 70 observations. Data are collected from Indonesian Capital Market Directory. This study uses path analysis to examine the hypothesis. The results show that (1) the influence of financial leverage on market capitalization is negative. (2) the influence of market capitalization on bid-ask spread is also negative. (3) the influence of financial leverage on the bid-ask spread is positive. (4) simultaneously, financial leverage and market capitalization have influence on bid-ask spread. Indirectly, financial leverage has influence on bid-ask spread through the market capitalization. Then, direct influence of financial leverage on the bid-ask spread is stronger than indirect influence of financial leverage on the bid-ask spread through the market capitalization. Therefore, it can be stated that the real influence of financial leverage on bid-ask spread is direct influence.Keywords: Bid-Ask Spread, Financial Leverage and Market Capitalization.